THE HUMERUS OF PROTEROTHERIIDAE (MAMMALIA, LITOPTERNA) AND ITS SYSTEMATIC USEFULNESS: THE CASE OF “PROTEROTHERIUM BERROI” KRAGLIEVICH, 1930 (Ameghiniana, 2018)
Proterotheriidae constitute a group of small-medium native South American ungulates with high diversity during the early Miocene and the late Miocene (Santacrucian and Huayquerian SALMAs). Recent studies demonstrated the wide dental variability, useful in the discrimination of the species. The aim of this work is to analyze the humerus as a postcranial element that is usually not found in association with cranial remains, and to evaluate (qualitatively and quantitatively) its systematic usefulness. We used the only known specimen of “Proterotherium berroi”, re-describing and re-illustrating it. The Principal Components Analysis resulted in 2 components explaining 86% of the variance. The PCA showed a differentiation between the largest species—Diadiaphorus majusculus and Anisolophus floweri—and the remaining ones (an intermediate group consisting of “Proterotherium”, Tetramerorhinus, Eoauchenia, Proterotheriidae indet., and the smallest, Thoatherium minusculum). We establish that, although there are slight morphological differences in the distal epiphysis of the humeri of Proterotheriidae, they mostly correspond to gradual changes in characters with continuous variations not linked to any particular taxonomic entity. These are not enough to assure a generic or specific determination, except for Eoauchenia. The differences in humeri size are considerable and they could be used as a criterion for discriminating Diadiaphorus and Anisolophus, to which the largest specimens would belong. We consider “P. berroi” a probable synonym of Neolicaphrium recens, but we ratify that a reliable systematic determination is only possible if it is based on cranial or dental remains.